The Effect of Notary Quality Improvement Training on Notary Performance at the Regional Office of the Ministry of Law and Human Rights of the Republic of Indonesia, South Sulawesi - Herlina Sakawati; Muhammad Fajri Syapar; Sulmiah Sulmiah (Jurnal Aktor, 2023)
This study aims to determine the impact of quality improvement training of notary position towards notary perfomance at Ministry of Law and Human Rights RI in South Sulawesi. To achieve this goal, the researchers used data collection techniques through observation, questionnaires and documentation. The data that has been obtained from the research results are processed using quantitative analysis to determine the impact of quality improvement training of notary position towards notary perfomance at Ministry of Law and Human Rights RI in South Sulawesi. This study uses quantitative research methods with sampling techniques using random sampling. The sample of this research is 47 notaries using the slovin formula. Collecting data using a questionnaire distributed to respondents. The results of the study showed that the Notary Public Quality Improvement Training was in the good category with a percentage of 78.7%. Then very good amounted to 9 people with a percentage of 19.1%. While the less good category is 1 person with a percentage of 2.1%. Notary performance at the Regional Office of the Ministry of Law & Human Rights of the Republic of Indonesia in South Sulawesi has a good performance category with a percentage of 87.2%. Then very good amounted to 6 people with a percentage of 12.8%.